THE INCORPORATION OF INFORMATION AND COMMUNICATION TECHNOLOGY TOOLS IN THE PRE-SERVICE LEARNING ACTIVITIES IN A TEACHER’S LESSON PLAN - Siti Drivoka Sulistyaningrum; Dian Pusparani (STKIP Siliwangi, 2021)
The advancement of Information and Communication Technology (ICT) has had a significant impact on the field of education, primarily in the areas of teaching English as a foreign language. However, the incorporation of ICT tools in pre-service teachers’ lesson plans for learning activities is still limited. As a result, the purpose of the research is to determine the types of ICT tools used in learning activities in pre-service teachers lesson plans. To answer the research questions, content analysis is used. The ten lesson plans are organized. The result showed that there are five types of learning activities. YouTube, PowerPoint, PowToon, Proprofs, Seesaw, Instagram, Movie Audio, Vizia, Audiobook, Winamp, and Google Form are among 11 types of ICT tools found in pre-service teacher’s lesson plans. Furthermore, all of the different types of learning activities are identified and listed as follows: 10 listening, 3 speaking, 3 reading, 9 writing, and 6 viewing. This finding suggests that pre-service teachers' lesson plans that incorporate information and communication technology act as content transmitters, presentational devices, and tools for directly engaging pre-service teachers and students on a platform. Keywords: ICT-based learning activities, ICT tools, Lesson Plan, Pre-Service Teacher.